The determinants of participation in savings groups and the impact on input investment among smallholder farmers in Sironko district, Uganda - Makhura, Moraka N. (University of Pretoria, 2022)
Mini Dissertation (MScAgric (Agricultural Economics))--University of Pretoria, 2022.